714 W all-fiber supercontinuum generation from an ytterbium-doped fiber amplifier. (June 2023) - Jiang, Li; Song, Rui; He, Jiuru; Hou, Jing
Highlights: An all-fiber supercontinuum with a record output power of 714 W is obtained. A broadband supercontinuum ranging from 690 nm to 2350 nm under maximum output power is achieved. The parameters that influence the output power and spectrum of SCare analyzed in detail. Abstract: An all-fiber supercontinuum (SC) source with record average output power of 714 W and spectrum ranging from 690 nm to 2350 nm is demonstrated. The method of SC generation from an ytterbium-doped fiber amplifier is used to achieve the high-power SC output. The source also exhibits a flat spectrum ranging from 1050 nm to 2095 nm at the −10 dB level. The parameters that influence the output power and spectrum of SC, including the pulse width of the seed laser and the passive fiber length in the last stage fiber amplifier, are analyzed in detail. To the best of our knowledge, the output power of SC in this work is the highest power that has been publicly reported. The scheme has the advantage of good robustness, which also has the potential to further increase the SC output power to the kilowatt level.